Arduino as an Educational Tool to Introduce Robotics - Plaza, Pedro; Sancristobal, Elio; Carro, German; Blazquez, Manuel; Garcia-Loro, Felix; Martin, Sergio; Perez, Clara; Castro, Manuel (2018 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE), 2018)
Short Description-The aim of this paper is to introduce the use of Arduino, an established tool in the development of applications and deployment of educational content, as of a course related to the introduction to robotics. Robotics requires several skills and competencies that can be easily developed with tools like Arduino. These skills and competencies are related to the areas of knowledge used for the development of robotic applications, such as computer science, electricity, electronics and mechanics. Throughout this paper we present Arduino, the resources used for the deployment of the course and the results obtained from the educational experiences carried out. The results of the educational robotics course demonstrate how children with previous experience in Scratch programming, skills and competencies with simple Crumble-based robots can continue the learning process through classroom experiences using Arduino. In this way, students can improve skills and competencies already worked with tools such as Scratch and Crumble. Another important observation from the results is that it is important to adapt the difficulty of the content to each child. Finally, it is important to combine theory and practice to include fun and intertwined tasks with the challenges of applying theory to problem solving.